KEBIASAAN SARAPAN PADA WANITA DI WILAYAH PERKOTAAN: HUBUNGANNYA DENGAN INDEKS MASSA TUBUH DAN PERSEN LEMAK TUBUH - Rini Oktaviani; Debby Endayani Safitri; Yuli Dwi Setyowati (ARGIPA (Arsip Gizi dan Pangan), 2021)
Breakfast is an activity of eating food in the morning. Skipping breakfast will lead to snack craving, which impact on excessive calorie intake then cause overweight. Women and men with a high percent body fat will experience a higher inflammatory process than women and men with a normal percent body fat. This study aims to determine the relationship between breakfast habits and percent body fat in adult women in urban areas. This study used a cross-sectional design with the criteria of the research subjects being women aged 19-25 years with low physical activity categories. This research was conducted in September-October 2020 when Large-Scale Social Restrictions were being implemented because the research site was in the red zone due to Covid-19. The research sample was 90 women, data collection on breakfast habits was obtained using a food recall questionnaire. Based on the results of the study, it can be concluded that breakfast habits are related to percent body fat (p<0.05), but not related to BMI (p>0.05), so it is recommended to get used to breakfast and eat a more diverse breakfast.